Atrial tachyarrhythmias in infants - Baksiene, Nijole Dalia; Sileikiene, Rima; Sileikis, Vytautas; Kevalas, Rimantas; Gurskis, Vaidotas (The Turkish Journal of Pediatrics, 2008)
This report describes clinical features and tactics of treatment of atrial tachyarrhythmias in infancy. Electrophysiologic study was performed in all 20 infants (2 weeks - 12 months old) in order to determine the mechanism of arrhythmia and to predict the clinical efficacy of management. Reciprocating mechanism was revealed in 12 infants. Atrial flutter was diagnosed for 10 infants among whom only 2 patients were older than two months. Six infants were found to have flutter conduction with a rate of 1:1. Four infants had congestive heart failure, 3 of them with a structurally normal heart. Half of the infants with atrial flutter needed long-term antiarrhythmic therapy. Electrotherapy for termination of atrial flutter was effective in all of them. Automatic atrial tachycardia in eight infants presented no major problems unless it became incessant and resistant to pharmacological treatment. The average tachycardia rate reached 171+/-7 beats/min. Atrial reciprocating tachycardia usually affects patients with diseased myocardium.